AN ANALYSIS OF FACTORS THAT AFFECTING STUDENT’S INTEREST IN FOLLOWING THE STUDENT ACTIVITY UNITS OF STMIK JAYANUSA - Reni Wijaya; Dorris Yadewani (Jurnal Apresiasi Ekonomi, 2019)
This study aims (1) To determine the factors that influence student interest in participating in Student activity units in STMIK Jayanusa and (2) The most dominant factors affecting the interest of STMIK Jayanusa students in participating in Student activity units.This research was carried out on the STMIK Jayanusa campus with a total response of 52 students who participated in the UKM. Data collected using questionnaires were analyzed by factor analysis through Statistical Program Social Scence (SPSS) 17.0 for Windows. The results of this study indicate that there are 3 factors that influence the participation of STMIK Jayanusa students in participating in Student activity units namely (a) The heredity factor has an eigenvalue of 2,284 with a variance value of 76.125%. Intelligence factor has an eigenvalue of 0.415 with a variance value of 13.833%. While environmental factors have an eigenvalue value of 0.301 with a variance value of 10.042%. and (2) The most dominant factor influencing student participation in participating in Student activity units is a factor that originates within students, namely the heredity factor of 76.125%